Metrology and analysis of nano-particulate barium titanate dielectric material - Allison, Matt (Kansas State University, 2007)
Since its discovery in the 1940's, barium titanate has become one of the more popular dielectric materials for use in discrete capacitors due to its high relative permittivity. Recently, consumer electronics have decreased in size, driving the need for smaller electronic components. To fill this need, researchers have created polycrystalline barium titanate with individual grains in the nanometer scale. With this decrease in size, many problems arise. This paper will outline the effects on the dielectric properties due to shrinking the individual grains, as well as discuss techniques for dielectric measurement of this material.
Keywords: Barium Titanate; Dielectric; Engineering, Electronics and Electrical (0544)